2020
DOI: 10.3389/fpsyt.2019.00981
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Sleep and Mood Disorders

Abstract: Editorial on the Research Topic Sleep And Mood DisordersSleep occupies almost one third of our life and it is necessary for survival of all species, including man. There is little doubt that sufficient, restorative sleep plays a critical role in maintaining physical and mental health. Evaluation of a good sleep always includes its quality, timing, quantity and rhythm. Sleep disturbances, including hypersomnia, insomnia, or irregular sleep patterns, result in various cognitive impairments and mood disorders (1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…We detected a high prevalence of insomnia symptoms (66.5%) in the early stages of substance withdrawal in patients admitted to a hospital detoxification unit. This rate is higher than the rates of 20-35% reported for the general population (2-6) and similar to rates described for patients with other psychiatric disorders (7)(8)(9)(10)(30)(31)(32). In a previous study, we found that 84.3% of addicted patients experienced insomnia symptoms during active consumption of substances (28).…”
Section: Discussionsupporting
confidence: 79%
“…We detected a high prevalence of insomnia symptoms (66.5%) in the early stages of substance withdrawal in patients admitted to a hospital detoxification unit. This rate is higher than the rates of 20-35% reported for the general population (2-6) and similar to rates described for patients with other psychiatric disorders (7)(8)(9)(10)(30)(31)(32). In a previous study, we found that 84.3% of addicted patients experienced insomnia symptoms during active consumption of substances (28).…”
Section: Discussionsupporting
confidence: 79%
“…The prevalence of depression (17%) and anxiety (8.5%) was beyond the expected for a group of employed young adults, suggesting an association of ISS with these disorders and possibly implying a common pathophysiology, both at a biological (Liu et al, 2018; Malhi & Mann, 2018; Nandam et al, 2020; Qin et al, 2016) and a psychological level (Li et al, 2016; Ruggiero et al, 2018). Moreover, chronic sleep deprivation is known to provoke mood disorders, depressive and/or manic, often associated with anxious symptoms, irritability, cognitive impairment and disinhibition (Fang et al, 2019; Lewis et al, 2017; Riemann et al, 2020; Verkhratsky et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“… 42 An underlying mechanism is that sleep deprivation can induce neuroinflammation including the activation of leucine-rich repeat protein-3 inflammasome, which then induces depressive-like behaviours, mood disorder and cognitive diseases. 43–45 The risk of hypertensive diseases increased by 36% among the extreme short sleepers. This supports the Sleep Heart Health Study, which showed that <6 hours of sleep increased the prevalence of hypertension by 66%.…”
Section: Discussionmentioning
confidence: 99%